Mapping of Danish Pharmacy Technician Students' Third-Year Projects in a Year with the COVID-19 Pandemic - Bjarke Abrahamsen; Rikke Nørgaard Hansen; Mette Skjøtt; Ditte Sloth-Lisbjerg; Charlotte Verner Rossing (MDPI AG, 2022)
To graduate, pharmacy technician students write a project in their third year. They choose between six elective courses, and work with a subject related to their education and everyday practice at community or hospital pharmacies. In this article, we report the mapping of third-year project themes and provide an overview of the challenges that COVID-19 pandemic restrictions have had on completing the projects. On the basis of all project titles, a list of themes was generated and described before all projects were allocated to one of the themes. Challenges experienced due to the COVID-19 pandemic were investigated from an analytical workshop where supervisors discussed their experience with supervising students throughout the completion of the projects. In total, 140 projects were included and thematised into eight themes: advanced pharmacy services, digital patient support, organisation and collaboration, handling of medicine, automated dose dispensing, medication counselling in community pharmacy, hospital pharmacy, and others, covering all six elective courses. The COVID-19 pandemic affected students' possibilities to collect data from either physical interviews or observations. The challenges prompted both constructive and creative discussions between students and supervisors to find ways to complete the projects, and required flexibility from all those involved: students, supervisors, community pharmacies, and hospital pharmacies. In conclusion, all students managed to complete their third-year project at a similar level of achievement statistically compared to average grades for the previous six years (2016-2020).